If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 3(4x + 2) + -2 Reorder the terms: 16 = 3(2 + 4x) + -2 16 = (2 * 3 + 4x * 3) + -2 16 = (6 + 12x) + -2 Reorder the terms: 16 = 6 + -2 + 12x Combine like terms: 6 + -2 = 4 16 = 4 + 12x Solving 16 = 4 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 16 + -12x = 4 + 12x + -12x Combine like terms: 12x + -12x = 0 16 + -12x = 4 + 0 16 + -12x = 4 Add '-16' to each side of the equation. 16 + -16 + -12x = 4 + -16 Combine like terms: 16 + -16 = 0 0 + -12x = 4 + -16 -12x = 4 + -16 Combine like terms: 4 + -16 = -12 -12x = -12 Divide each side by '-12'. x = 1 Simplifying x = 1
| 108-24= | | 8x+6=2x-30 | | 6m+3=33 | | 9x-8=5x+5 | | 0.5*n(n-3)=54 | | -3x-17=-2 | | 8x-2+3x=13x+8 | | -11=x+16 | | 11w=3520 | | z-3=30 | | 10c=70 | | 5w+6=9w+3 | | q-6=6 | | 4=m-2 | | 12+g=16 | | t+15=19 | | sqrt(3x+2)=xsqrt(2) | | 12=((-3+1)(-3+1))(k) | | =x^4-6x^3+13*x^2-12*x+5 | | 0.5x(x-3)=54 | | x=2(6+2x)+8x | | 8x-20=2x-8 | | A=5*5*5(3.5) | | w+3/4=6 | | 3x+2=x^2-2 | | px^2-6x+p=0 | | 2x-36+x=90 | | 3x=2+5 | | 3j-9=6 | | 4x^2y-6xy^2=u | | 3x+x+2+4=18 | | x^2+x^2=c |